Znaczenie aspektów ekonomicznych w formułowaniu wizji oraz misji do realizacji celów strategicznych przedsiębiorstwa - Adamkiewicz-Drwiłło, Hanna G. (Meaning of economic aspects in for mulating for realization of strategic aims of enterprise the vision as well as mission, 2006)
The effectiveness of activity of present enterprise depends in large measure from correctly the formulated long-term vision and connected with her - the mission . It in present study was accepted that the economic connected with profit formulated in vision as well as mission of enterprise closely aspects can make up foundation which determines long-term his success. It in corroboration of that hypothesis the visions as well as missions, were quoted was the chosen corporations, working on international market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 13-19